The messenger [compact disc, unabridged] - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2006)
Gabriel Allon, an art restorer and spy, faces the greatest challenge of his life. An al-Qaeda suspect is killed in London, and photographs are found on his computer. These photographs lead Israeli intelligence to suspect that al-Qaeda is planning one of its most audacious attacks ever. Will Allon, who's still recovering from his last grueling showdown, find strength to halt this terrorist plot?